2015
DOI: 10.1016/j.nutres.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Food environments are relevant to recruitment and adherence in dietary modification trials

Abstract: Few studies have examined the built environment's role in recruitment to and adherence in dietary intervention trials. Using data from a randomized dietary modification trial of urban Latina breast cancer survivors, we tested the hypotheses that neighborhood produce access could act as a potential barrier and/or facilitator to recruitment, and that a participant's produce availability would be associated with increased fruit/vegetable intake, one of the intervention's targets. Eligible women who lived within a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 39 publications
(35 reference statements)
0
15
1
Order By: Relevance
“…Our findings are the opposite of Wedick et al 10 and Feathers et al 11 who found that a more supportive food environment (e.g., greater access to Green Carts, farmers’ markets, and supermarkets) was associated with improved intervention-related outcomes. However, these prior studies included interventions focused on reducing dietary fat and increasing fruit, vegetable, and fiber consumption, and both were set in urban areas of the Northeastern United States.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our findings are the opposite of Wedick et al 10 and Feathers et al 11 who found that a more supportive food environment (e.g., greater access to Green Carts, farmers’ markets, and supermarkets) was associated with improved intervention-related outcomes. However, these prior studies included interventions focused on reducing dietary fat and increasing fruit, vegetable, and fiber consumption, and both were set in urban areas of the Northeastern United States.…”
Section: Discussioncontrasting
confidence: 99%
“…In correlational analyses, we generally found small but statistically significant improvements in diet and PA among those who lived in less favorable food and PA environments, contrary to our original hypothesis, and to previous findings in urban settings. 10, 11, 13, 42 In adjusted analyses, which controlled for baseline values of outcomes and socio-demographic variables, findings again indicated that those who lived in less favorable environments lost more weight and increased PA to a greater degree than those in healthier, more supportive environments. Our results could suggest a hypothesis to be tested in rural settings: when resources are less plentiful, intrinsic motivation may influence an individual’s ability to make healthy changes to a greater degree than supportive environments and community resources.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…And Feathers et al. (), in a secondary analysis of data from an intervention designed to increase fruit and vegetable intake, found no statistically significant relationship between intervention adherence and density of retail produce locations near home for the 53 out of 70 women enrolled in the intervention for whom data were available. A key limitation in the literature is that existing research is based on relatively small sample sizes that may lack the statistical power to reliably measure treatment effect heterogeneity.…”
Section: Discussionmentioning
confidence: 99%